Mothers' involvement in play activities of preschool-aged children in low socioeconomic status families - Custodio, Tracey Mae J.; Romero, Sarah A.; Agustin, Estrella R. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
Play and parent involvement are perceived to be important for the growth and development of children. These two were examined in this study as it aims to know the play activities of children, involvement of mothers to children's play activities, and mothers' intentions to their involvement. Using descriptive research method, 30 Filipino mothers of pre-school-aged children residing in a barangay in Quezon City were interviewed with a semi-structured questionnaire. The findings of the study showed that kunwariang laro and larong kalye are the kinds of play children mostly engaged in indoors and outdoors respectively. Results showed that preschool-aged children play more outdoors than indoors. Their indoor playmates were their siblings, while their outdoor playmates were their neighbors. For mothers involvement, findings showed that mothers participate more in children's indoor play activities than outdoors they facilitate their children's play by choosing play venue and buying toys for them, and indirectly supervise their children. Mothers engage in harutan to strengthen mother-child relationships, and they buy interest-based toys to provide children's desires while mothers indirectly supervising their children to secure their safety and avoid conflict from other children. All in all, these findings indicate that children utilize available space and materials in their surroundings, mothers are restrictive with their children's actions to ensure their and security, and mothers' intentions and involvements are significantly affected by their environment.
submitted June 2017
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Play -- Philippines; Education, Preschool -- Philippines -- Parent participation